The deepest record of the octocoral Acanthogorgia from the Red Sea - Macrina, Laura; Nolan, Megan K. B.; Terraneo, Tullia I.; Oury, Nicolas; Augustin, Nico; van der Zwan, Froukje M.; Benzoni, Francesca (Frontiers in Marine Science, 2024)
Octocorals (Cnidaria: Anthozoa) have a global distribution and form benthic assemblages along the depth gradient, from shallow to deep waters. They often occur below SCUBA diving limits, where they can become dominant habitat builders and aggregate different taxa. During a cruise in February 2023, one octocoral specimen was collected at 1453 m depth at Kebrit Deep, in the northern Saudi Arabian Red Sea axis, an area with extremely high temperature and salinity profiles at depth. Morphological analysis coupled with DNA barcoding using two mitochondrial markers (COI and mtMuts), revealed that the coral belongs to Acanthogorgia, a genus of azooxanthellate octocorals known to occur from 3 to 2300 m depths in cold, temperate and tropical waters. In the Red Sea, the genus was previously only known from shallower waters. Hence, we report the deepest record of the genus Acanthogorgia from the warm and saline Red Sea basin. This finding provides novel insights on deep-water octocoral diversity in the Red Sea, a still scantily explored area of the world, while emphasizing the need for further explorations at depth.